If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -4x = 7x + -9 + 10 Reorder the terms: 6 + -4x = -9 + 10 + 7x Combine like terms: -9 + 10 = 1 6 + -4x = 1 + 7x Solving 6 + -4x = 1 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 6 + -4x + -7x = 1 + 7x + -7x Combine like terms: -4x + -7x = -11x 6 + -11x = 1 + 7x + -7x Combine like terms: 7x + -7x = 0 6 + -11x = 1 + 0 6 + -11x = 1 Add '-6' to each side of the equation. 6 + -6 + -11x = 1 + -6 Combine like terms: 6 + -6 = 0 0 + -11x = 1 + -6 -11x = 1 + -6 Combine like terms: 1 + -6 = -5 -11x = -5 Divide each side by '-11'. x = 0.4545454545 Simplifying x = 0.4545454545
| 24a-22=-1(1-6a) | | y(y+2)=63 | | -12x^2y+8xy=0 | | (-12x^2)y+8xy=0 | | y(y+2)=48 | | 7z=8z^2 | | -0.7x+8.45=-0.3x+7.25 | | y(y-7)=44 | | -2v+8=-4v+4 | | 3x-6x-15=27 | | 4/5x2-6/y | | .16y+.16=.125y+.8 | | 2(3x+7)=-6+2 | | -11m=-99 | | y(y-3)=-2 | | -11m=99 | | 7z=8Z*2 | | y(y+8)=65 | | (4-2x)/5+3=9 | | -0.1x+0.4x-8=-2 | | 750=20d | | 12x-42=8x-18 | | 10z-19-3z+5=0 | | 65t=130(t-3) | | (11x+2)/6=4 | | x/8-4=-6 | | 11x+2/6=4 | | 2-x-2/5y=0 | | 2x-5+29=180 | | Isy=x+2linear | | 2x-5+29=90 | | -x+9=-29 |